(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The research is based on explaining the different scenes of lightning in the poetry of the obscure from the Granada era, and it is represented in studying lightning from two aspects. The first aspect is dealing with lightning based on it being a reality, and what it includes of its clear elements of brilliance, light, speed, heat and other than that, and employing it in the service of the idea. As for the second aspect, it is based on the things for which the elements of lightning are brought in the images of simile, metaphor and noun metonymy, such as the mouth, the hand, the false promise and the face, and all of that is accompanied by poetic evidence, indicating the aspect that the poet intends in lightning.